Early Detection of Heavy Metal Pollution with Biological Markers in Freshwater Clam (Corbicula javanica) in Maros River, Indonesia - Erni Indrawati; Ratnawati Ratnawati; Hadijah Hadijah; Rizal Akbar Alydan; Jalil Jalil; Dahlifah Dahlifah (Jurnal Perikanan UGM (Journal of Fisheries Sciences), 2026)
This study aims to determine suitable biomarkers as monitoring tools for detecting heavy metal pollution in the Maros River. The analysis results showed that the livers of Corbicula javanica from the Maros River contained metallothionein Pb and metallothionein Cd. The average accumulation values of Pb and Cd that induced the appearance of metallothionein Pb were 0.001628 ppm and 0.004929 ppm, respectively. This study demonstrates that Corbicula javanica clams exhibit a significant biological response to exposure to heavy metals Pb and Cd in the Maros River, as evidenced by high bioaccumulation levels, the presence of the molecular biomarker metallothionein, and disturbances in physiological parameters such as the Gonad Somatic Index (GSI). Cd exhibited higher and faster accumulation patterns and Bioaccumulation Factor (BCF) values compared to Pb, indicating stronger toxicity potential and biological retention. The expression of Cd and Pb metallothionein in liver tissue, which appeared in the first and fifth weeks of exposure, demonstrated the high sensitivity of these biomarkers as early detection tools for heavy metal contamination. Conversely, although the GSI values of river freshwater clam were significantly lower than those of the control group, this parameter proved less sensitive to specific metal types, making it unsuitable as a sole indicator for early detection of contamination. The positive correlation between metal concentrations in tissues and shifts in physiological distribution, as determined by Principal Component Analysis (PCA), further supports the finding that freshwater clams experience stress accumulation over time. Based on the results obtained, Pb metallothionein and Cd metallothionein are biological markers (biomarkers) that can be used as tools for early detection of water pollution.